The development of English grammar and reading comprehension by majority and minority language children in a bilingual primary school - Steinlen, Anja K. (Studies in Second Language Learning and Teaching, 2017)
Both for the first language (L1) and for all additional languages (L2 or L3), grammatical knowledge plays a vital role in understanding texts (e.g., Grabe, 2005). However, little is known about the development and interaction of grammar and reading comprehension in beginning foreign language learning, especially with respect to children with a minority language background. This longitudinal study, therefore, examined minority and majority language children’s English grammar and reading comprehension skills. The children attended a German-English partial immersion primary school and were tested at the end of Grades 3 and 4. As expected, we found grammar to affect reading comprehension but also reverse effects. Most importantly, the results did not reveal any differences between the two language groups, irrespective of the test. Therefore, immersion primary school programs seem to be suitable for minority language children, and these children do not automatically represent an at-risk group for foreign language learning.